Design and fabrication of an automatic classifying smart trash bin based on Internet of Things - Sun, Bo; Quanjin, Ma; Zhu, Guangxu; Yao, Hao; Yang, Zidong; Da Peng, ,; Mohd Ruzaimi, Mat Rejab (Elsevier, 2021)
Municipal solid waste (MSW) is an increasing waste resource and challenging task to solve environmental pollution and waste collection problems. The smart trash bin is sufficient equipment to reduce human intervention and improve living conditions, lacking multifunctional purposes. To solve the problem that traditional trash can lacks self-identification of recyclable garbage and nonrecyclable garbage, a smart trash bin based on WiFi environment and Arduino control is proposed. The smart trash bin takes Arduino as its master controller and interacts with Arduino in the WiFi environment to realize automatic garbage classification and communication between people and trash bin. This paper aims to describe the hardware and software design ideas of trash bins in the implementation process, and the mechanism of garbage classification and the application of the Internet of things in garbage recycling are emphatically studied. The results indicate that the system can run stably and achieve accurate classification within 2 seconds, which reduces the waste of resources, changes the traditional garbage management mode, improves management efficiency, and realizes recycling of garbage.